Evaluation of Lantana camara Linn. Stem for Pulp and Paper Making - Naithani, Sanjay; Pande, P. K. (Indian Forester, 2009)
Lantana camara Linn. Is a noxious weed posing a serious threat to the ecology. It demands concrete efforts for its management. L. camara was evaluated for its pulp and paper making properties. Data on chemical constituents, fibre dimensions, unbleached, bleached yield and physical strength properties of pulp sheets were obtained. Parameters of proximate chemicals and fibre morphology were non-significantly different for samples and replications (Î± = 0.05). The unbleached pulp yields under different pulping process were 50.5-44.6%. Laboratory hand made pulp sheets with adequate strength properties were obtained from soda, soda-sulphite and kraft pulps prepared from L. camara plant material.